Practices Of Collaborative Learning In English Classes - Dhami, Jagdish (Journal of Advanced Academic Research, 2025)
Avoiding the teaching of English as a subject in the far western region, the secondary level has gradually adopted an adaptive language policy and co-constructed learning space where learners are obliged to collaborate with each other while sharing responsibilities for educational outcomes. By taking this collaborative method, it highlights that students are crucial components, and in turn compassion, accountability to both parties, and patience are strongly served. This study investigates the practice of collaborative learning activities in secondary English classrooms, with particular emphasis on teachers’ beliefs and practices. Through qualitative data from both educators and students, the article discusses that cooperative learning has significant motivational rewards with regard to student-centric improvements in academic performance. This is also true in English Language Teaching, for which employing these activity learning techniques results in more engaged students who gain a greater understanding of language structure; therefore, learning a second or foreign language becomes a smoother process. This study employed qualitative research methodology to gather data from semi-structured interviews with teachers and students, as well as classroom observation, to provide deep insight into how collaborative learning is applied in practice and its importance for English education. The study also discusses resource limitations and the lack of adequate training for teachers working in these rural environments. We found evidence suggesting that engaging in these joint activities results in interactive classrooms where students use language with greater freedom and meaning. The results indicate outcomes of student-centered teaching strategies that have been endorsed in international research and provide concrete examples of how collaborative learning can be used to enhance language learning performance. These challenges aside, merging learning cultivates an active and inviting classroom climate, benefits academic language, oracy, and strategies, as well as working characteristics, all serving student engagement success.